2019
DOI: 10.1177/1070496519854505
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the “Certification Gap” for Different Types of Oil Palm Smallholders in Riau Province, Indonesia

Abstract: Indonesia is the world’s largest producer of palm oil, and its smallholder oil palm plantations involve more than 2.3 million farmers. The rapid expansion of the oil palm area, and resulting negative environmental and social impacts, has increased the demand for sustainability certification for palm oil products. This study investigates whether different types of smallholders face different barriers in complying with certification standards. The study uses survey data from 829 smallholders in Riau, Sumatra. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 47 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…In fact, not all oil palm farmers can meet certification requirements. Smallholders who are already RSPO certified can meet certification requirements of up to 70%, but non-certified smallholders have the highest gap between RSPO requirements and field practice [23]. Based on research conducted by Rietberg and Slingerland, there are 56 audit findings in 10 recertification reports for independent farmers [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, not all oil palm farmers can meet certification requirements. Smallholders who are already RSPO certified can meet certification requirements of up to 70%, but non-certified smallholders have the highest gap between RSPO requirements and field practice [23]. Based on research conducted by Rietberg and Slingerland, there are 56 audit findings in 10 recertification reports for independent farmers [24].…”
Section: Resultsmentioning
confidence: 99%
“…Based on research conducted by Rietberg and Slingerland, there are 56 audit findings in 10 recertification reports for independent farmers [24]. The biggest challenge of the RSPO certification requirements for palm oil smallholders is Principle 2 (regulation and law), Principle 4 (conservation and environment) and Principle 6 (community and employee) [23]. Given the limited knowledge of the certification requirements, assistance is necessary for oil palm farmers.…”
Section: Resultsmentioning
confidence: 99%
“…Cappucci (2018) describes this as a “valley” of lower returns where portfolios first absorb the costs of sustainability integration before the promised benefits materialize. In the case of palm oil, growers are particularly encumbered by such additional financial burdens such as a membership fee and various administrative costs arising from monitoring and reporting (Brandi et al, 2015; Hutabarat, Slingerland, & Dries, 2019). However, notwithstanding the RSPO standard, certified companies continue to be price‐takers in a competitive market.…”
Section: Discussionmentioning
confidence: 99%
“…Independent smallholders are the focus of the studies because they are facing challenges in adopting the certification. The results showed that smallholders generally lack the knowledge, skill, financial capabilities and resources to implement the certification on their own [45,47,50].…”
Section: Socio-economic Componentmentioning
confidence: 99%